Health care practitioners' views of the support women, partners, and the couple relationship require for birth trauma: current practice and potential improvements. (2020) - Delicate, Amy; Ayers, Susan; McMullen, Sarah
Abstract: Aim: To examine health care practitioners' views of the support women, partners, and the couple relationship require when affected by birth trauma, barriers to gaining such support, and potential improvements. Background: Ongoing distress following psychologically traumatic childbirth, also known as birth trauma, can affect women, partners, and the couple relationship. Birth trauma can lead to post traumatic stress symptoms (PTSS) or disorder (PTSD). Whilst there is a clear system of care for a PTSD diagnosis, support for the more prevalent experience of birth trauma is not well-defined. Method: An online survey of health care practitioners' views of the support parents require for birth trauma, barriers to accessing support, and potential improvements. Practitioners were recruited in 2018 and the sample for the results presented in the article ranged from 95 to 110. Results: Practitioners reported differing needs of support for women, partners, and the couple as a unit. There was correlation between practitioners reporting having the skills and knowledge to support couples and feeling confident in giving support. The support most commonly offered by practitioners to reduce the impact on the couple relationship was listening to the couple. However practitioners perceived the most effective support was referral to a debriefing service. Practitioners observed several barriers to both providing support and parents accessing support, and improvements to birth trauma support were suggested. Conclusions: Practitioners indicate that some women, partners, and the couple as a unit require support with birth trauma and that barriers exist to accessing effective support. The support that is currently provided often conflicts with practitioners' perception of what is most effective. Practitioners indicate a need to improve the identification of parents who need support with birth trauma, and more suitable services to support them.